2007
DOI: 10.1016/j.neulet.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Complex changes in ecto-nucleoside 5′-triphosphate diphosphohydrolase expression in hypoxanthine phosphoribosyl transferase deficiency

Abstract: Lesch-Nyhan disease is caused by a deficiency of the purine salvage enzyme, hypoxanthine phosphoribosyl transferase (HPRT). The link between HPRT deficiency and the neuropsychiatric symptoms is unknown. In rat B103 neuroblastoma cell membranes and mouse Neuro2a neuroblastoma cell membranes, nucleoside 5 -triphosphatase (NTPase) activity is substantially reduced, whereas in fibroblast membranes from HPRT knock-out mice, NTPase activity is increased. Candidate genes for these NTPase activity changes are ecto-nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…During the measurement of the ATP affinity of ecAT3.10, continuous bath perfusion conditions were employed in order to continuously replenish ATP and control the extracellular ATP concentration. Physiologically, however, ectonucleotidases contribute to purinergic signaling dynamics by clearing extracellular ATP by hydrolysis[ 27 , 58 ], thereby generating ADP, AMP, and adenosine, which can act independently as purinergic signals. In order to test ecAT3.10’s ability to detect endogenous ectonucleotidase activity[ 58 ], we performed experiments in which a single addition of exogenous ATP was made to cultured Neuro2A cells expressing ecAT3.10 in an imaging dish under static bath conditions without solution exchange.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the measurement of the ATP affinity of ecAT3.10, continuous bath perfusion conditions were employed in order to continuously replenish ATP and control the extracellular ATP concentration. Physiologically, however, ectonucleotidases contribute to purinergic signaling dynamics by clearing extracellular ATP by hydrolysis[ 27 , 58 ], thereby generating ADP, AMP, and adenosine, which can act independently as purinergic signals. In order to test ecAT3.10’s ability to detect endogenous ectonucleotidase activity[ 58 ], we performed experiments in which a single addition of exogenous ATP was made to cultured Neuro2A cells expressing ecAT3.10 in an imaging dish under static bath conditions without solution exchange.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically, however, ectonucleotidases contribute to purinergic signaling dynamics by clearing extracellular ATP by hydrolysis[ 27 , 58 ], thereby generating ADP, AMP, and adenosine, which can act independently as purinergic signals. In order to test ecAT3.10’s ability to detect endogenous ectonucleotidase activity[ 58 ], we performed experiments in which a single addition of exogenous ATP was made to cultured Neuro2A cells expressing ecAT3.10 in an imaging dish under static bath conditions without solution exchange. We initially used Neuro2A cells because they express the ectonucleotidase NTPDase1 (CD39)[ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…TaqMan probes and SYBR Green reagents were from Applied Biosystems (Darmstadt, Germany). Sources of other reagents have been described elsewhere (Pinto et al 2005(Pinto et al , 2008Pinto and Seifert 2006;Lorenz et al 2007;Erdorf et al 2011a).…”
Section: Methodsmentioning
confidence: 99%
“…In HPRT-deficient cells, 6-thioguanine cannot be converted to the cytotoxic 6-thioguanosine 5′-triphosphate and hence, cells survive (Zoref-Shani et al 1993;Hacke et al 2012). HPRTdeficient B103 cells are an established cell culture model for LND and have already been used for two decades to study various aspects of the pathophysiology of LND including alterations in neuronal differentiation, nucleotide metabolism, purinoceptor function, nucleotidase activity, nucleotidase gene expression, and adenylyl cyclase (AC) regulation (Zoref-Shani et al 1993;Ma et al 2001;Connolly 2001;Pinto et al 2005;Pinto and Seifert 2006;Lorenz et al 2007;Erdorf et al 2011a).…”
mentioning
confidence: 99%
“…A series of evidences have suggested that these enzymes may be involved in eukaryotic events such as: virulence (Berredo-Pinho et al, 2001), purinergic signaling (Deaglio and Robson, 2011;Knowles, 2011), inflammation (Kannan, 2002), hemostasis (Bernardes et al, 2000;Jin et al, 2005;Marcus et al, 2005), purine salvage (de Souza Leite et al, 2007;Lorenz et al, 2007) and host-pathogen interactions (Bisaggio et al, 2003;Matin and Khan, 2008).…”
Section: Introductionmentioning
confidence: 99%